Evaluación del impacto de un ensayo comunitario sobre la lactancia materna en zonas de Conchamarca y El Valle. Huánuco 2013 - De La Mata Huapaya, Rosario (2017)
The objective of the research was to evaluate the impact of a community intervention on exclusive breastfeeding in the district Conchamarca and El Valle, Huanuco , 2012. To this end an experimental study of the type of field test was designed. We worked with two manipulative field groups . We worked with two manipulated groups (30 pregnant Conchamarca area and 30 pregnant Valley area). Data were obtained from the leaves of collection; performing an inferential analysis of the chi - square test obtained p : α = 3.84 0.05 < 63.4 . Accepting H1. Thus it concluded : 70% of the sample stated that students in community practices apply educational methods and techniques ; 83.3% of pregnant women in areas Conchamarca and 76.7 % of the valley were found satisfied on education through the methods and techniques applied in the community trial in exclusive breastfeeding.